Neuropsychiatry revisited: epilepsy as the borderland between neurology and psychiatry - Sone, Daichi; Kanemoto, Kousuke (Frontiers in Psychiatry, 2024)
Since epilepsy is often complicated by psychiatric symptoms, the contributions of psychiatry are indispensable for the care and improvement of the quality of life of individuals with epilepsy. Moreover, the existence of a bidirectional relationship between epilepsy and psychiatric symptoms was recently proposed, based on the evidence that not only are some psychiatric symptoms more likely than others to follow epilepsy, but also that psychiatric symptoms may precede the onset of epilepsy and the presence of psychiatric symptoms may influence the outcome of treatment for seizures. There has also been a gradual accumulation of neurobiological findings related to psychosis, depressive, and anxiety symptoms that are associated with epilepsy with respect to abnormalities in brain networks and neurotransmission. This mini-review focuses on the neuropsychiatric aspects of epilepsy and proposes that a reconsideration of neuropsychiatry in light of epilepsy findings could serve as a bridge between psychiatry and neurology.